2021
DOI: 10.1002/ejlt.202000367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interfacial Activity of Eugenol and Eugenol Esters with Different Alkyl Chain Lengths on Inhibiting Sunflower Oil Oxidation

Abstract: Effects of eugenol esters with different alkyl chain lengths and combinations of eugenol + eugenol esters on sunflower oil oxidation at 338, 358, and 378 K are evaluated by determining different kinetic parameters. Also, water content and reverse micelles size of sunflower oil samples are monitored during oxidation. Eugenyl acetate shows higher antioxidant activity than eugenol in sunflower oil, while eugenyl butyrate, eugenyl hexanoate, and eugenyl decanoate shows lower antioxidant activity than eugenol. Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It has been confirmed that the general trend of the oxidation process tends to change at temperatures higher than 60 °C (Zheng et al, 2020). Although the reaction rate also increases, the effect of the pathway change is much higher than the reaction rate (Keramat et al, 2021). Second, the effects of temperature on antioxidant molecules which can cause decomposition or evaporation.…”
Section: Temperature and Curcumin Functionmentioning
confidence: 87%
“…It has been confirmed that the general trend of the oxidation process tends to change at temperatures higher than 60 °C (Zheng et al, 2020). Although the reaction rate also increases, the effect of the pathway change is much higher than the reaction rate (Keramat et al, 2021). Second, the effects of temperature on antioxidant molecules which can cause decomposition or evaporation.…”
Section: Temperature and Curcumin Functionmentioning
confidence: 87%
“…Then, excess of anhydrides and produced acids were evaporated from the mixture by evaporation under vacuum. Sesamol esters purity (>95%) was measured via gas chromatography/flame ionization detector by the method of Keramat, Golmakani, and Toorani (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…This indicates and describes the synergy contribution to the inhibition of chain initiation and/or propagation reactions and the likelihood of their promoted incorporations into the interfacial area of association colloids [ 56 ]. Additionally, sunflower oil samples containing eugenol + eugenyl acetate and eugenol and eugenyl butyrate exhibited better efficiency than eugenol alone, which could be related to the better accessibility of eugenol to the interfacial region of the reverse micelles when eugenyl acetate and eugenyl butyrate are present [ 57 ].…”
Section: Recent Advances In Reducing the Oxidation Rate Of Bulk Oilmentioning
confidence: 99%